2021
DOI: 10.3390/electronics10131534
|View full text |Cite
|
Sign up to set email alerts
|

On the Improvement of the Isolation Forest Algorithm for Outlier Detection with Streaming Data

Abstract: In recent years, detecting anomalies in real-world computer networks has become a more and more challenging task due to the steady increase of high-volume, high-speed and high-dimensional streaming data, for which ground truth information is not available. Efficient detection schemes applied on networked embedded devices need to be fast and memory-constrained, and must be capable of dealing with concept drifts when they occur. Different approaches for unsupervised online outlier detection have been designed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…With respect to sig attr , as of now, we relied on the supervised RF-SHAP-feature importance scoring functionality for better result interpretability. However, in future evaluation, we want to replace RF with an online unsupervised OD algorithm equipped with a feature importance scoring functionality, such as Loda [23] or PCB-iForest [13]. As we showed that the ambitious aim to exploit the outcome of OD algorithms in order to generate an attack pattern generally works, we would also want to investigate the impacts of introducing FPs and FNs on signature comparison.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…With respect to sig attr , as of now, we relied on the supervised RF-SHAP-feature importance scoring functionality for better result interpretability. However, in future evaluation, we want to replace RF with an online unsupervised OD algorithm equipped with a feature importance scoring functionality, such as Loda [23] or PCB-iForest [13]. As we showed that the ambitious aim to exploit the outcome of OD algorithms in order to generate an attack pattern generally works, we would also want to investigate the impacts of introducing FPs and FNs on signature comparison.…”
Section: Discussionmentioning
confidence: 99%
“…As already pointed out, in particular, the missing ground truth values in evolving (theoretically infinite) data that demand real or almost near real-time processing, taking the evolution and speed of data into account, require unsupervised OD methods capable of dealing with SD. We consider OD on SD, as is the context in [13]. Widely accepted and popular solutions, such as Hoeffding Trees [14] or Online Random Forests [15], achieve good accuracy and robustness in data streams [16] but are not designed to operate on unlabeled data.…”
Section: Related Work 21 Aspects On Unsupervised Online Outlier Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the scope of our future work is also to apply xStream in the windowed setting and check which mode-sequential or parallel-is in general more effective and why. Since UFSSOD's main purpose is the streaming feature selection for outlier detection, further evaluation should also include the latest online outlier detection methods, e.g., PCB-iForest [70].…”
Section: Discussionmentioning
confidence: 99%